Dampak fatherless terhadap perilaku delinkuensi pada remaja - Arifah, Elvi Nisaul (Maliki Interdisciplinary Journal, 2025)
Childhood is a fundamental period in shaping a person's character and psychological development. One issue that has received great attention is the condition of fatherlessness, namely the absence of a father figure, whether physical, emotional or social. In the modern era, this phenomenon is increasingly encountered due to various factors such as divorce, death, or the absence of the father's active role in the family. Fatherlessness has the potential to affect children's psychological development, especially during adolescence, and can increase the risk of delinquent behavior such as juvenile delinquency and digital deviance, including addiction to online pornography (cyberporn). Lack of adult supervision and guidance is also a factor that increases the possibility of delinquent behavior in adolescents. This study emphasizes the importance of early intervention and holistic support, such as emotional rehabilitation programs, better supervision, and access to adequate education and guidance. The hope is that this research can provide new insights for families, communities and policy makers in dealing with the impact of fatherlessness on adolescent behavior.